Comparison of the effectiveness of two adjustable negative pressure ureteral access sheaths combined with flex ureteroscopy for ≤ 2 cm renal stones - Cui, Deheng; Ma, Qinghong; Xie, Shengbiao; Wang, Guangzhi; Li, Guanghai; Chen, Guoqiang (Scientific reports, 2024)
To compare the safety and effectiveness of the combination of intelligent intrarenal pressure control platforms (IPCP) and flexible ureteral access sheath (FUAS) combined with retrograde intrarenal surgery (RIRS) for the treatment of renal stones less than 2 cm. We retrospectively collected 383 patients with renal stones who underwent RIRS in our department from June 2022 to October 2023. Inclusion criteria: stone length or the sum of multiple stone lengths ≤ 2 cm. Finally, 99 cases were included and divided into an IPCP group (n = 40) and FUAS group (n = 59) based on surgical methods. The main endpoint was the stone-free rate (SFR) at third months after surgery, with no residual stones or stone fragments less than 2 mm defined as stone clearance. The secondary endpoints were surgical time and perioperative complications, including fever, sepsis, septic shock, and perirenal hematoma. There was no statistically significant difference in general information between the two groups, including age, gender, body mass index, comorbidities, stone side, stone location, stone length, urine bacterial culture, and hydronephrosis. The operation time for IPCP group and FUAS group was 56.83 ± 21.33 vs 55.47 ± 19.69 min (p = 0.747). The SFR of IPCP group and FUAS group on the first postoperative day was 75.00% vs 91.50% (p = 0.024). The SFR was 90.00% vs 94.90% in the third month (p = 0.349).In IPCP group, there were 11 cases with stones located in the lower renal calyces and 17 cases in FUAS group. The SFR of the two groups on the first day and third months after surgery were 45.50% vs 88.20% (p = 0.014) and 63.60% vs 94.10% (p = 0.040), respectively, with statistical differences. For kidney stones ≤ 2 cm, there was no difference in SFR and the incidence of infection-related complications between IPCP and FUAS combined with RIRS, both of which were superior to T-RIRS. For lower renal caliceal stones, FUAS has a higher SFR compared to IPCP.